Adolescents' and mothers' temperament types and their roles in early adolescents' socioemotional functioning. (September 2018) - Hirvonen, Riikka; Väänänen, Johanna; Aunola, Kaisa; Ahonen, Timo; Kiuru, Noona
The present study examined adolescents' and mothers' temperament types and their roles in the socioemotional functioning of early adolescents. A total of 869 sixth-grade students and 668 mothers participated in the study. The students rated their temperament and socioemotional functioning and the mothers rated their own temperament. Latent profile analyses identified four temperament types among the adolescents (resilient, reserved, average, and mixed) and three types among the mothers (resilient, average, and mixed). The results showed that the adolescents with resilient or reserved temperaments reported significantly fewer conduct problems and emotional symptoms, less hyperactivity, and higher prosociality than adolescents with a mixed temperament type. The most adaptive adolescent–mother temperament matches were between a resilient or reserved adolescent and a resilient or average mother; these adolescents reported the highest levels of socioemotional functioning. Mothers with mixed or average temperaments were related to fewer conduct problems and emotional symptoms and less hyperactivity among adolescents with a mixed temperament, while mothers with a resilient temperament type were beneficial for prosocial behavior among adolescents with a mixed temperament. These findings increase understanding of the role of temperament and the interplay between adolescents' and mothers' temperaments in the development of early adolescents' socioemotional adjustment.